2019
DOI: 10.1007/978-3-030-12974-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Grasses for Rehabilitating Degraded African Drylands

Abstract: Drylands provide an important livelihood stream to its inhabitants across the globe through a range of products and ecosystem services. However, these fragile ecosystems are threatened and believed to experience various degrees of land degradation. Estimates of the landmass affected by land degradation in the global drylands range from 10 to 20%, a percentage that is increasing at an annual global rate of 12 million ha of soil lost from desertification and drought. African drylands are especially highly suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In drylands, the importance of Poaceae species extends from the cultivation of grasslands and erosion control to, and especially, uses by humans (e.g., supply of cereals) and livestock (e.g., fodder and forage) ( Capstaff and Miller, 2018 ; Mganga et al, 2019 ). More than half of the population’s food supply is provided by three grass crops (i.e., rice, wheat, and maize) which are particularly important in developing countries where they provide food security and nutrition to local populations ( Tadele, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In drylands, the importance of Poaceae species extends from the cultivation of grasslands and erosion control to, and especially, uses by humans (e.g., supply of cereals) and livestock (e.g., fodder and forage) ( Capstaff and Miller, 2018 ; Mganga et al, 2019 ). More than half of the population’s food supply is provided by three grass crops (i.e., rice, wheat, and maize) which are particularly important in developing countries where they provide food security and nutrition to local populations ( Tadele, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, taller plants of E. macrostachyus compared to C. ciliaris and E. superba suggest its higher capacity in absorbing the kinetic energy of raindrops and subsequently protecting the ground from the explosive impact that breaks soil aggregates and weakening its structure. Rainfall simulation studies conducted in semi-arid African rangelands (e.g., Nyangito et al, 2009;Mganga et al, 2019) have demonstrated that grass height contributed significantly to reducing sediment loss in reseeded African rangelands. Moreover, taller grasses are more suitable for reducing grazing pressure because they are readily accessible to grazing herbivores.…”
Section: Commelina Bengalensis (Wandering Jew)mentioning
confidence: 99%
“…A key aspect of RinD that was implemented by the restoration project, is the use of planned comparisons, an approach where farmers compare and test promising options, and variations thereof, in their fields across a varying range of ecological and socioeconomic conditions [3][4][5]24,25]. Ref.…”
Section: Methodsmentioning
confidence: 99%
“…However, low survival rates of planted trees, especially species highly valued by farmers, is a major limitation in the drylands [19,20]. This is partly due to unreliable rainfall, high levels of land degradation resulting in low soil productivity, planting of ecologically unsuitable tree species, and poor tree seedling management practices [18,19,24].…”
Section: Introductionmentioning
confidence: 99%